Euclid preparation: LXI. Cosmic Dawn Survey: ' Pre-launch' multiwavelength catalogues for Euclid Deep Field North and Euclid Deep Field Fornax - Zalesky, L.; Mcpartland, C. J.R.; Weaver, J. R.; Toft, S.; Sanders, D. B.; Mobasher, B.; Suzuki, N.; Szapudi, I.; Valdes, I.; Murphree, G.; Chartab, N.; Allen, N.; et al. (EDP Sciences, 2025)
The Cosmic Dawn Survey (DAWN survey) provides multiwavelength (UV/optical to mid-IR) data across the combined 59 deg2 of the Euclid Deep and Auxiliary fields (EDFs and EAFs). In this work, the first public data release from the DAWN survey is presented. The catalogues made available herein consist of a subset of the full DAWN survey that includes two EDFs: EDF North (EDF-N) and EDF Fornax (EDF-F). Each field has been covered by the ongoing Hawaii Twenty Square Degree Survey (H20), which includes imaging from the CFHT MegaCam in the u filter and from the Subaru Hyper Suprime-Cam (HSC) in the griz filters. Each field has been further covered by Spitzer/IRAC 3.6-4.5μm imaging spanning 10 deg2 and reaching ∼25 mag AB (5Ï). All present H20 imaging and all publicly available imaging from the aforementioned facilities were combined with the deep Spitzer/IRAC data to create source catalogues spanning a total area of 16.87 deg2 in EDF-N and 2.85 deg2 in EDF-F for this first release. These catalogues are referred to as the pre-launch (PL), as Euclid data is not yet public for these fields and therefore it is not included. Photometry was measured from these multiwavelength data using The Farmer, a novel and well validated model-based photometry code. Photometric redshifts and stellar masses were computed using two independent codes for modelling spectral energy distributions: EAZY and LePhare. Photometric redshifts show good agreement with spectroscopic redshifts (ÏNMAD ∼ 0.5, η < 8% at i < 25). Number counts, photometric redshifts and stellar masses were further validated in comparison to the COSMOS2020 catalogue. The DAWN survey PL catalogues are designed to be of immediate use in these two EDFs and will be continuously updated and made available as both new ground-based data and spaced-based data from Euclid are acquired and made public. Future data releases will provide catalogues of all EDFs and EAFs and include Euclid data.
Keywords: Catalogs; Editorials, notices; Galaxies: general; Miscellaneous; Surveys